Mongolias economic prospects resource-rich and landlocked between two giants. - Helble, Matthias; Hill, Hal; Magee, Declan (Metro Manila, Philippines Asian Development Bank, 2020)
This book examines Mongolias recent economic development and outlines reforms that would help the country take advantage of its many opportunities. Mongolia is a resource-rich country that, despite being landlocked, is well-placed to take advantage of trade with its two giant neighbors. To maximize the countrys potential, the government can improve macroeconomic management, enhance the skill base, and provide hard and soft infrastructure to promote trade and efficient logistics. Governance and institutional reforms are also crucial.
Keywords: Economic development; Developing countries -- Economic conditions; Macroeconomics -- Mongolia; Economics -- Research; Electronic books